Kontribusi Emotional Spiritual Quotient (ESQ) Dalam Pembelajaran Pendidikan Agama Islam (Jurnal Sosial Humaniora dan Pendidikan, 2024)
This research aims to determine the contribution of the Emotional Spiritual Quotient (ESQ) aspect in learning Islamic Religious Education. The approach used in this research is a qualitative approach with library research methods. The data analysis technique used is content analysis. The results of this research conclude that the contribution of the Emotional Spiritual Quotient (ESQ) aspect in Islamic Religious Education learning includes faith and piety, noble character, honesty, discipline, responsibility, caring (mutual cooperation, cooperation, tolerance, peace), polite, responsive and pro- Actively confident in interacting with family, friends, teachers, environment and society.